2018
DOI: 10.5944/ap.15.2.22256
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency, Meaning in Life, and Life Satisfaction: An Examination of Moderating Effects

Abstract: While presence of meaning in life (i.e., presence) is associated with a plethora of desirable qualities (e.g., greater well-being, longevity, positive affect), search for meaning is associated with psychological distress (e.g., reports of conflict, rumination, depression; Boyle, Barnes, Buchman, & Bennett, 2009). Individuals with higher resiliency, defined as a multifaceted competency in adapting and recovering from adversity, could potentially mitigate the distress associated with search, and thus, achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
6
0
1
Order By: Relevance
“…The results regarding the importance of individual resilience for life satisfaction is as expected and it is consistent with the findings of other studies (Beutel et al, 2009;Lau et al, 2018). It is understandable that people who assess that they can cope more easily with life's challenges and recover more quickly are more satisfied with life than those who find it more difficult to overcome challenges.…”
Section: Predictorssupporting
confidence: 90%
See 1 more Smart Citation
“…The results regarding the importance of individual resilience for life satisfaction is as expected and it is consistent with the findings of other studies (Beutel et al, 2009;Lau et al, 2018). It is understandable that people who assess that they can cope more easily with life's challenges and recover more quickly are more satisfied with life than those who find it more difficult to overcome challenges.…”
Section: Predictorssupporting
confidence: 90%
“…It must be mentioned that researchers who considered resilience as a personality trait equated the term resiliency with resilience, but the dominant view in the literature is that the two terms should be considered separately because it has been found that resilience cannot be a personality trait because resources in the environment can play an even greater role in coping with adversity than individual resources (Liebenberg VanderPlaat and Dolan, 2020). Resiliency is positively associated with life satisfaction (Beutel, Glaesmer, Decker, Fischbeck and Brähler, 2009;Lau, Feher, Wilson, Babcock and Saklofske, 2018) and has been shown to reduce the negative effects associated with ACE by strengthening the mechanisms of coping with stress, emotional intelligence, and overall functioning (Flynn, Parnes and Conner, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Giving meaning to life is a category of existential thinking that is dependent on an individual's attitude toward life 25 . According to the conducted research, ascribing meaning to problems and suffering is a fundamental aspect of living purposefully, adapting to stress, and enduring distress 26 . Research investigating the relationship between meaning in life and psychopathology has demonstrated that a low level of meaning in life is associated with various mental health issues, such as addiction disorders, depression, hopelessness, and suicide 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it could not be detached from the place where the person lives (physical zone) as the context. The concept of a comfort zone is aligned with the concept of satisfaction with life which has a positive correlation with resiliency [ 36 ], and a sense of relatedness to others which is a protective factor of resiliency [ 37 ]. Also, a sense of place and individual attachment to a rural area, either physical or psychological, were found to play an essential role in doctor retention [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%